2020
DOI: 10.1523/jneurosci.0356-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

β4-Nicotinic Receptors Are Critically Involved in Reward-Related Behaviors and Self-Regulation of Nicotine Reinforcement

Abstract: Nicotine addiction, through smoking, is the principal cause of preventable mortality worldwide. Human genome-wide association studies have linked polymorphisms in the CHRNA5-CHRNA3-CHRNB4 gene cluster, coding for the a5, a3, and b4 nicotinic acetylcholine receptor (nAChR) subunits, to nicotine addiction. b4*nAChRs have been implicated in nicotine withdrawal, aversion, and reinforcement. Here we show that b4*nAChRs also are involved in non-nicotinemediated responses that may predispose to addiction-related beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 70 publications
(96 reference statements)
3
14
0
Order By: Relevance
“…We observed that, on average, WT mice titrate their intake to achieve a consistent nicotine dose, in agreement with previous reports 12,34,35 , and discovered that mutant mice lacking the nAChR β4 subunit did not, resulting in greater nicotine intake, notably at high nicotine concentrations in the drinking solution. These behavioral results are in agreement with the greater intracranial self-administration observed at high nicotine doses in these mice 33 and, conversely, with the results obtained with transgenic TABAC mice overexpressing the β4 subunit at endogenous sites, which avoid nicotine and consequently consume very little 13,33 . Nevertheless, it should be noted that conflicting results have also been reported regarding the role of β4 nAChRs in nicotine consumption.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed that, on average, WT mice titrate their intake to achieve a consistent nicotine dose, in agreement with previous reports 12,34,35 , and discovered that mutant mice lacking the nAChR β4 subunit did not, resulting in greater nicotine intake, notably at high nicotine concentrations in the drinking solution. These behavioral results are in agreement with the greater intracranial self-administration observed at high nicotine doses in these mice 33 and, conversely, with the results obtained with transgenic TABAC mice overexpressing the β4 subunit at endogenous sites, which avoid nicotine and consequently consume very little 13,33 . Nevertheless, it should be noted that conflicting results have also been reported regarding the role of β4 nAChRs in nicotine consumption.…”
Section: Discussionsupporting
confidence: 90%
“…Representative currents and average responses following a puff application of nicotine (30 μM, 200 ms) on IPN neurons from β4 −/− mice transduced in the IPN with either lenti-pGK-β4-IRES-GFP (KO-β4 IPN , n = 7 neurons from 2 mice, I = −362 ± 95 pA) or lenti-pGK-GFP (KO-GFP IPN , n = 7 neurons from 1 mouse, I = −71 ± 18 pA; Mann-Whitney test, p = 0.004). C. Average nicotine intake was lower in KO-β4 IPN than in KO-GFP IPN (two-way repeated measure; ANOVA: genotype x dose interaction, F[3, 99] = 6.3, ***p < 0.001; main effect of dose, F[3, 99] = 69.1 ***p < 0.001, effect of genotype, F[1, 33] = 6.637, *p = 0.015). D. Ternary diagram representing each β4 −/− mouse, transduced with either β4 or GFP, and illustrating its nicotine consumption index over its side bias index.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, central GLP-1 signaling modulates nicotine intake via the habenular–interpeduncular pathway ( 25 ). Given that the habenular–interpeduncular pathway is particularly enriched with α5- and β4-nAChRs ( 34 , 35 ) and site-specific loss- and gain-of-function models have demonstrated key roles for both receptor subunits in governing nicotine consumption ( 17 , 18 ), neural crosstalk between GLP-1R and nAChR signaling might be relevant to this neurobiology. To evaluate this, we exposed α5 KO, β4 KO, and WT mice to a pharmacological treatment study with the long-acting GLP-1R agonist liraglutide ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the α5-α3-β4 ( CHRNA5-CHRNA3-CHRNB4 ) gene cluster has been linked to smoking heaviness, nicotine dependence ( 17–21 ), and higher body mass index (BMI) ( 22 , 23 ). Animal studies have implicated all individual subunits of the α5-α3-β4 gene cluster in regulating nicotine consumption (titration of reward and aversion) ( 17 , 18 , 24 ). However, despite a clear implication of α5 and β4 in nicotine sensitivity, the role of these subunits in food reward has received very little attention.…”
mentioning
confidence: 99%